La música ecuatoriana en el fortalecimiento de la identidad cultural de las y los jóvenes del oratorio pastoral de la cuasi-parroquia nuestra Señora de los Dolores de Carigán de la ciudad de Loja. Periodo 2014-2015 - Andrade Armijos, Romel Danilo (2016)
Identify the level of knowledge of the Ecuadorian music by the survey population of Pastoral Oratorio quasi-parish of Our Lady of Sorrows of Carigan, in order to promote the musical genres of Ecuador and strengthen their cultural identity is the goal with which part of this project. To do the research universe was delimited and methods as scientific, statistical and inductive as support for this research, as well as techniques such as interview the same as it was applied to two authorities, and the survey 2 teachers, 30 parents used family and 30 young people, giving a total population of 64 people. The results show a 61.67% believe that music is an incentive to cultural development and personal training, a result that served to raise a proposal that relates to a guitar workshop using Ecuadorian genres adapted to religious music. It is concluded that the lack of musical artistic workshops is the reason why there is a consolidation of its own cultural identity; therefore it is recommended to implement a cultural artistic activity, the development of workshops related to the field of music, being a source of inspiration and attraction for the youth of the institution and the sector.